Mladá slavistika V Slavistická badatelská dílna - Demelová, Jana (Masaryk University Press, 2020)
Title in English: Young Slavonic Studies V: Scholarly Workshop in Slavonic Studies Young Slavistics V is the eighth consecutive volume in a series of annual publications by doctoral students from the Department of Slavonic Studies in Brno. There are eight studies by doctoral students in different Slavonic fields, in which the students focus on specific chosen topics of Slavonic literature, languages and cultures. Their writings are based on research done for dissertations currently being prepared. Therefore, the publication is a presentation of current research topics being addressed in Brno by young students of Slavonic Studies, and at the same time the texts indicate the trends in contemporary Slavonic research among this emerging generation of scholars.